Satu ujikaji pembinaan tingkah laku asertif di kalangan pemimpin persatuan mahasiswa, sebuah universiti tempatan - Ahmad Fadil, Bin Jaafar. (1997)
The objective of this study was to examine the effect of assertive training for purpose of building assertive behaviour, among student union leaders of a local university. An experience was conducted on 120 participants of the Nation Building Course, Biro Tatanegara (Perak branch), Prime Minister Department the Biro Tatanegara camp (Perlis branch) in Kaki Bukit, Perlis. They were divided into four 'dynamic groups', based on 'Solomon Four Groups Design' (Solomon, 1978). They were systematically suddivided into four 'dynamic groups' according to alphabetical order. Finally, based on the finding the researcher believed that assertive training could build assertive behaviour respondents through the test in the study.